(untitled) (Update Dental College Journal, 2013)
Background : Ovarian diseases and infertility are the very common health problems among the female population. Alteration in the volume of the ovary occurs throughout the reproductive life which may predispose to ovarian diseases such as cyst, polycystic ovary and ovarian carcinoma. Moreover, the reduction in ovarian volume leading to decrease the fertility of a women also. So the present study is designed to assess the volume of the ovary in Bangladeshi women in different age groups which will provide a complete and standarize the data in Bangladeshi population and also compare the data with other countries. It will provide resourcefull information which may further determine the ovarian reserve and reproductive age of female for improving the accurate diagnosis and management of ovarian diseases as well as infertility problems. Study design: Cross sectional and analytical type of study. Materials: The present study was performed on 65 cadaveric ovaries of both side in Bangladeshi female age ranging from 5 years to 65 years. Methods: The samples were divided into four different age groups. They were group A or prepubertal group (5-12years), group B or reproductive group (13-45 years), group C or perimenopausal group (46-51years) and group D or postmenopausal group (52-65years). Results: The mean (±SD) volumes were 2.84 + 0.22 milliliter and 2.83±0.24 milliliter in group A, 8.64 + 0.89 milliliter and 8.61± 0.89 milliliter in group B, 6.85 + 0.79 milliliter and 6.84±0.76 milliliter in group C and 2.62 + 0. 52 milliliter and 2.61± 0.50 milliliter in group D in the right & left ovaries respectively. The highest mean volume was observed in group B and lowest mean volume was in group D in both ovaries. Statistically highly significant difference (P<0.001) were found when group A was compared with group B & C, group B was compared with group C & D and group C was compared with group D. But when group A was compared with group D, it was not significant (P<0.50).The mean difference in volumes of right and left ovary between group A, group B, group C and group D were statistically not significant. Conclusion: In this study, volume of the ovary does not vary in between right and left ovary in any age group. DOI: http://dx.doi.org/10.3329/updcj.v2i2.15482 Update Dent. Coll. j: 2012; 2 (2): 08-12